The Role of the Saber Extortion Task Force (Sweeping Illegal Charges Task Force) In The Eradication of Criminal Acts of Corruption - Jupri Jupri; A. ST Kumala Ilyas; Suardi Rais; Rusmulyadi Rusmulyadi; Saharuddin Saharuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Indonesia is still classified as a country that is in a position of corruption based on the results of the release of Transparency International Indonesia. Even in cases of criminal acts of corruption have reached remote areas. To suppress this rate, the central government to the regions then formed a Task Force for Sweeping Illegal Charges (Satgas Saber Extortion). Has a role to take action against and prevent the occurrence of criminal acts of corruption in the community. This study aims to determine the role of Saber Pungli in eradicating corruption. The research method used is normative-empirical legal research. The results of the study show that Saber Pungli is not yet optimal in carrying out corruption eradication work in the regions.